Virtual Reality Medical Training for COVID-19 Swab Testing and Proper Handling of Personal Protective Equipment: Development and Usability - Zikas, Paul; Kateros, Steve; Lydatakis, Nick; Kentros, Mike; Geronikolakis, Efstratios; Kamarianakis, Manos; Evangelou, Giannis; Kartsonaki, Ioanna; Apostolou, Achilles; Birrenbach, Tanja; Exadaktylos, Aristomenis K.; Sauter, Thomas C.; et al. (Frontiers in Virtual Reality, 2022)
Efficient and riskless training of healthcare professionals is imperative as the battle against the Covid-19 pandemic still rages. Advancements in the field of Virtual Reality (VR), both in software and hardware level, unlocked the true potential of VR medical education. An example of such an advancement is the "Covid-19: Virtual Reality Strikes Back" VR application, presented in this work. The main objective of this simulation is to help train medical personnel and volunteers in properly performing Covid-19 swab testing and using protective measures, based on a world-standard hygiene protocol. The learning procedure is carried out in a gamified way that facilitates skill transfer from virtual to real world, with performance that matches and even exceeds traditional methods.